Karakteristik Mikroemulsi Ekstrak Bunga Kamboja Kuning (Plumeria alba) Pada Ukuran Partikel dan Waktu Ekstraksi - Wiradharma, I Gede Yudha; Suhendra, Lutfi; Wrasiati, Luh Putu (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
The yellow frangipani flower (Plumeria alba) possesses numerous important chemicals that can be utilized in the formulation of cosmetic and fragrance goods by PEG 400 extract microemulsion. In the extraction of yellow frangipani blossoms, PEG 400 serves as a polar solvent with a low molecular weight, non-adhesive properties, and a dielectric constant of 13.6. The study aimed to ascertain the influence of particle size and extraction duration on the microemulsion properties of yellow frangipani flower extract, as well as to identify the optimal conditions for achieving superior microemulsion characteristics of the extract. This research employed a Randomized Group Design featuring two variables. The initial factor is particle size, categorized into three levels: 40 mesh, 60 mesh, and 80 mesh. The second component is extraction duration, comprising three levels: 2 hours, 4 hours, and 6 hours. Data were subjected to ANOVA analysis, subsequently followed by Tukey's test. The findings indicated that the interplay between particle size and extraction duration markedly influenced microemulsion stability following 24 hours of incubation and subsequent centrifugation stability. The ideal treatment comprised a microemulsion of yellow frangipani flower extract at a particle size of 80 mesh, extracted over a duration of 6 hours, exhibiting a clear appearance. The turbidity index was measured at 1.378% after 24 hours of incubation, with a centrifugation stability of 1.522%, a particle size of 9.476 nm, and a stable microemulsion.